Mechanism to Detect Pesticide Residues in Tealeaves Based on CdZnSe/ZnS Ternary Alloy Quantum Dots - Hai, Nguyen Ngọc; Yen, Nguyen Hai; Giang, Duong Thi; Cuong, Dinh Hung; Nhat, Nguyen Duc; Nga, Pham Thu; Cao, Dao Tran (Communications in Physics, 2015)
In this report, we present the optical properties of the biosensors fabricated from CdZnSe/ZnS quantum dots. The optical properties such as absorption and emission of the ternary quantum dots before and after coupling with the protein molecules like streptavidine (SA) and acetylcholinesterase enzymes (AChE), to form a biosensor structure, will be presented. In particular, the changes in luminescence intensity according to the pH value of the solution environment containing biosensor have been considered, before and after the presence of pesticides. The changes in luminescence intensity of the biosensor after the presence of pesticide over time from 2 seconds to 26 minutes were also surveyed. We have been carried out the tests to determine the trace amounts of commercial pesticides like Motox 5EC, containing 5% cypermethrin and Tungatin 10 EC, containing 10% abamectin, on the real samples of tealeaves. Some characteristics of the relationship between composition, structure, and special optical properties of ternary alloy quantum dots will also be presented. These studies open up the potential applications of  ternary quantum dots for agricultural production.